2017
DOI: 10.1021/jacs.6b10490
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent CdSe Superstructures: A Nanocluster Superlattice and a Nanoporous Crystal

Abstract: Superstructures, combining nanoscopic constituents into micrometer-size assemblies, have a great potential for utilization of the size-dependent quantum-confinement properties in multifunctional electronic and optoelectronic devices. Two diverse superstructures of nanoscopic CdSe were prepared using solvothermal conversion of the same cadmium selenophenolate precursor (MeN)[Cd(SePh)]: the first is a superlattice of monodisperse [CdSe(SePh)(dmf)] nanoclusters; the second is a unique porous CdSe crystal. Nanoclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 120 publications
2
15
0
Order By: Relevance
“…Notably, the tetrahedral CdSe units are observed in several metal chalcogenide nanoclusters that containing selenolate co‐ligands. [ 20,63 ] The strongly binding X‐type ligands seem to play critical role in directing the growth of tetrahedral CdSe nanoclusters as they can stabilize the surface through different binding modes. A PDF analysis of the CdSe (417 nm) MSCs, having absorption spectrum similar to (CdSe) 34 , has shown that it has non‐zinc‐blende structure, supporting the theoretical predictions of the non‐zinc‐blende‐type structures in stoichiometric clusters.…”
Section: Atomic Structures: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the tetrahedral CdSe units are observed in several metal chalcogenide nanoclusters that containing selenolate co‐ligands. [ 20,63 ] The strongly binding X‐type ligands seem to play critical role in directing the growth of tetrahedral CdSe nanoclusters as they can stabilize the surface through different binding modes. A PDF analysis of the CdSe (417 nm) MSCs, having absorption spectrum similar to (CdSe) 34 , has shown that it has non‐zinc‐blende structure, supporting the theoretical predictions of the non‐zinc‐blende‐type structures in stoichiometric clusters.…”
Section: Atomic Structures: Theoretical Approachmentioning
confidence: 99%
“…They contain a nonstoichiometric metal to chalcogenide ratio (non 1:1) with metal being predominant compared to chalcogenide, making them regarded as nonstoichiometric nanoclusters. [ 63,67,68 ] The presence of X‐type ligands perhaps induces nonstoichiometry as they could balance the charge of excess metal cations. For instance, some of the size‐selected and purified MSCs displayed in Figure 2C are shown to be Cd‐rich with Cd/Se atomic ratios in the range of 1.1–1.3.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14] NPs exhibit a wide range of functionality because their optoelectronic properties and chemical reactivity can be easily tuned by changing either the composition, [15][16] surface ligands, [17][18][19][20][21] and/or their size and morphology. [22][23][24][25] NPs have a high surface-tovolume ratio where different surface functional groups and surface defects strongly affect their optoelectronic and chemical properties. Therefore, obtaining a molecular level depiction of the surface of NPs is important from both a fundamental and applied perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Atomically precise group II–VI semiconductor quantum dots (QDs) with 1–2 nm in diameter are of interest, for example, due to narrow size distribution for improved control of spectral tuning, for understanding QD formation and growth, e.g., to direct the ultimate shape, or in formation of CdSe superstructures that result in solid state emission at room temperature . In addition, although the two-photon absorption cross-section could be smaller in such clusters, the response is still much larger than for molecular systems (values larger than 10 3 GM were measured).…”
Section: Introductionmentioning
confidence: 99%